Aktivitas Imunostimulan Ekstrak Metanol Biji Kurma (Phoenix dactylifera) secara In Silico Terhadap Reseptor GIF dan COX-2 serta Uji In Vitro melalui Proliferasi Sel Limfosit Mencit - Siti Warnasih; Tamimah Shafwatul Ishlah; Dianda Namira Azzahra; Gita Syahputra (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
Dates (Phoenix dactylifera) is one of the plants that very useful, but the date palm seeds that become waste have not been widely used. Based on studies that are known to contain bioactive compounds that can be suspected as antioxidants, antimicrobials and anti-inflammatory. However, research on immunostimulants from dates, especially in silico and in vitro, has not been widely carried out. Therefore, this study aims to determine the potential of date seed bioactive compounds as immunostimulants through in silico against Human Glycosylation-Inhibiting Factor (1GIF) and Human Cyclooxygenase-2 (5IKR) receptors as well as in vitro through the proliferation of lymphocyte cells of male mice (Mus musculus) balb/c strains with the MTT Assay methods. The results of the in silico study showed that 5-O-Caffeoylshikimic Acid had the highest interaction and stability, Gibbs free energy with 1GIF and 5IKR receptors, -6.68 kcal/mol and -8.58 kcal/mol, respectively. This value is known to be higher than the Caffeic Acid as control ligand. The results of in vitro research obtained methanol extract of date seeds at a concentration series of 6.25; 12.5; 25 µg/mL had higher lymphocyte cell proliferation activity which was indicated by an increasing OD value, and at a concentration of 25 μg/mL produces the highest immunostimulant activity. Therefore, date seed extract containing the compound 5-O-Caffeoylshikimic Acid can potentially be an immunostimulant agent.